Detection of chemical warfare agent related phenylarsenic compounds and multibiomarker responses in cod (Gadus morhua) from munition dumpsites. (December 2020) - Niemikoski, Hanna; Straumer, Katharina; Ahvo, Aino; Turja, Raisa; Brenner, Matthias; Rautanen, Tomi; Lang, Thomas; Lehtonen, Kari K.; Vanninen, Paula
Abstract: Recently, sea-dumped chemical weapons (CWs) containing toxic chemical warfare agents (CWAs) have raised international attention. It is well known that CWAs are leaking from corroded munitions causing a risk to the surrounding marine environment, while the impact on marine biota is still unknown. In this study, cod ( Gadus morhua ) was used as a model species to study the possible bioaccumulation of phenylarsenic CWAs and their negative effects at multiple levels of biological organization on fish living in the vicinity of a major CWs dumpsite in the Bornholm Basin in the Baltic Sea. In total, 14% of the cod muscle samples collected close to the main dumpsite contained trace levels of phenylarsenic CWAs. However, most of the biomarkers measured did not show clear differences between this area compared with a lesser contaminated reference area. On the other hand, significant changes in some biomarkers were observed in individuals containing trace levels of CWA-related chemicals. The results gained in this study have significant importance for environmental risk assessment and for evaluating the risk of CWA contamination for human seafood consumers. Highlights: The first study providing information on bioaccumulation and tissue distribution of CWAs in cod from the Baltic Sea. 14% of the analyzed cod muscle samples contained traces of CWA-related chemicals (ng g −1 ). Changes in some biomarker responses are related to individuals with CWA accumulation in tissues. The biomarker response did not differ markedly between the contaminated and less contaminated areas.